Answers

2015-06-26T23:32:12+08:00

1. x²-16×+64=0                 (x-8) (x-8)=0                                                

                                    x-8=0                x-8=0                                                

                                  x-8+8=0+8            x-8+8=0+8                                                                                                  x=8                     x=8

2.2s²+85-10=0                        2s²=-85+10  

                                                 2s²=-75

                                                  /2     /2     -> divide by two 

                                                s²=-75 -> get the squareroot.

                                                 s=+-5 the square root of 3

NOTE: -75 is not a perfect square right? so we have to find two factors that either of them is a perfect square so I equated 25 and -3. since 25 is a perfect square, I equated its square root which is 5 . you can identify the rest :) if you are confused, youre free to ask. hehe my explanation is so hard to understand XD

                                                 

1 3 1